Proposed new interior design of Black Cube ICT one-stop centre at No 17 Jalan Persiaran Dataran 2, Bandar Seri Iskandar, 32600, Perak for Black Cube / Siti Khairina Khalid - Khalid, Siti Khairina (Faculty of Architecture, Planning and Surveying, 2012)
Each student that is in the final semester of Diploma in Interior Design must come up with a project that covers the interior aspect in terms of design. Students must understand the project, client’s need as well as study the site and building of the proposed site. The project that has been selected for my final project is ICT one-stop center at Lot 17, Jalan Persiaran Dataran 2, Bandar Seri Iskandar, 32600, Bota, Perak for Black Cube. The first Black Cube store was opened in Universiti Putra Malaysia, Serdang. Black Cube mainly targets IPT students to help them in receiving the best sales and services available. Black Cube provides services as well as consultations on anything we wish to inquire. Since the Information Communication & technology is a growing field among the students, Black Cube has taken the opportunity to open a few brances in campuses. The main objective of this project is to help in creating effective spaces for an ICT one-stop center as well as producing a suitable image. The image and concept that has been chosen must reflect the client’s corporate image and also suitable for their nature of business. Various methods have been carried out in order to complete this project research. From interviewing the client, going through articles and observing the surrounding. Studies on the site and building needed to be done in order to understand the structure as well as its suitability. In conclusion, each and every data collection must be done carefully in order to achieve a successful design.